The Effect of Using Digital Interactive Boards (DIB) on Fifth-Grade Elementary School Students’ Literacy Comprehension of Intrinsic Elements - Ninin Murni Ayunani; Abdul Hafid; Solehun Solehun (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the effect of using Digital Interactive Boards (DIB) on fifth-grade elementary school students’ literacy comprehension of intrinsic elements. The main problem in this study is the low ability of students to understand the intrinsic elements of texts due to the use of less interactive learning methods. This study employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The research sample consisted of two classes, namely the control class and the experimental class, selected using a cluster random sampling technique. The instrument used was a test of comprehension of the intrinsic elements of texts. The results showed that the average score of the experimental class increased significantly from 55.15 to 92.08, while the control class increased from 54.47 to 68.13. The paired sample t-test results indicated a significant improvement in both groups, but the improvement was higher in the experimental class. In addition, the independent sample t-test results showed a significant difference between the two groups (Sig. < 0.05). Based on these findings, it can be concluded that the use of Digital Interactive Boards (DIB) has a significant effect on improving students’ literacy comprehension of intrinsic elements. This study implies that the integration of technology in learning can improve the effectiveness and equity of students’ learning outcomes. Therefore, DIB can be used as an innovative alternative learning medium to improve the quality of Indonesian language learning in elementary schools.